2010
DOI: 10.3324/haematol.2010.025825
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and functional characterization of allogantigen-specific anergic T cells suitable for cell therapy

Abstract: Background CD4+ regulatory T cells are a specialized subset of T cells that actively control immune responses. Several experimental protocols have been used to expand natural regulatory T cells and to generate adaptive type 1 regulatory T cells for regulatory T-cell-based therapies. Design and MethodsThe ability of exogenous recombinant human interleukin-10 to induce alloantigen-specific anergy in T cells was investigated and compared to that of interleukin-10 derived from tolerogenic dendritic cells, in mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(91 citation statements)
references
References 60 publications
5
86
0
Order By: Relevance
“…In addition, our data sustain the key role of IL-10 in DC-10-induced T-cell anergy (and Tr1 cells), 27,[43][44][45] since, in a limited number of donors, T cells primed with HLA-G low DC-10 became hypo-responsive to secondary stimulation. Data presented in this study demonstrated that, although IL-10-derived by DC-10 is necessary to promote T-cell anergy, it is not sufficient to promote the differentiation of Tr1 cells at high frequency.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In addition, our data sustain the key role of IL-10 in DC-10-induced T-cell anergy (and Tr1 cells), 27,[43][44][45] since, in a limited number of donors, T cells primed with HLA-G low DC-10 became hypo-responsive to secondary stimulation. Data presented in this study demonstrated that, although IL-10-derived by DC-10 is necessary to promote T-cell anergy, it is not sufficient to promote the differentiation of Tr1 cells at high frequency.…”
Section: Discussionsupporting
confidence: 74%
“…[40][41][42][43] We have demonstrated that IL-10, either exogenously added or derived by DC-10, inhibited the proliferation of allogeneic naïve T cells in vitro. 44,45 DC-10 promote Tr1 cell differentiation via the IL-10-induced HLA-G/ILT4 pathway.27 Although IL-10, ILT4, and HLA-G are important for DC-10 tolerogenic activity, their relative contributions in inducing Tr1 cells were not investigated. The identification of DC-10 that spontaneously expressed high or low HLA-G finally allowed us to demonstrate that the high levels of HLA-G on DC-10 are required for efficient induction of anergic T cells, and consequently Tr1 cells.…”
mentioning
confidence: 99%
“…The high expression levels of HLA-G and the high IL-10/IL-12 production ratio render DC-10 potent inducers of allo-specific Tr1 cells [24,83]. The clinical use of DC-10 relies on this latter feature, and clinical-grade protocols for the induction of allo-specific Tr1 cells, suitable for cell therapy, using DC-10 have been developed [84,85]. In addition to this clinical application, we are currently testing the potential use of DC-10 as cell therapy for tolerogenic DCbased approaches [7,11].…”
Section: Dcs As Tolerogenic Cell Productmentioning
confidence: 99%
“…In fact, donor T cells primed ex vivo with host APCs and IL-10 are anergic towards host-HLA antigens but contain host-specific Tr1 cells and memory T cells able to respond to pathogens [93]. The five patients treated with this approach showed improved immune reconstitution, and four of them are alive with complete disease remission at 7.2 years (range 6.4-8.3) after HSCT [94,95], thus providing the first proof-of-concept of feasibility and safety of Tr1 cellbased therapy and suggesting a clinical benefit of the use of Tr1 cells after HLA-haploidentical HSCT.…”
Section: Adoptive Transfer Of Regulatory T Cells For Prevention Of Gvhdmentioning
confidence: 99%